Alumina ceramic and brazing method thereof

Through the metallization treatment of alumina ceramic substrates and the step-by-step slow cooling process under vacuum environment, combined with the use of BNi-9 welding sheets, the cracks and oxidation corrosion problems of ceramic brazed joints under high temperature conditions are solved, and the high performance and long-term stability of ceramic materials are achieved at high temperatures.

CN119638473AInactive Publication Date: 2025-03-18LEADING THIN FILM MATERIALS (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411832281.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119638473A_ABST
    Figure CN119638473A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic brazing, and provides aluminum oxide ceramic and a brazing method thereof, and the brazing method comprises the processes of metallization treatment, assembly, heat treatment and the like. According to the method, the problem that a brazed joint cracks is solved, and the phenomenon of oxidation corrosion of a weld joint is avoided. By adopting the method, the aluminum oxide ceramic with good performance can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic brazing, and in particular to an alumina ceramic and a brazing method thereof. Background Art

[0002] Ceramic materials exhibit excellent corrosion resistance and thermal stability under high temperature conditions, and therefore have been widely used in a variety of fields such as aerospace, energy and chemical engineering. However, the disadvantages of ceramic materials, such as difficult processing and poor toughness, limit their full application. Therefore, combining ceramics with metals has become an effective solution to overcome these limitations. Currently commonly used connection methods, such as diffusion welding and active brazing, usually cannot meet the requirements for long-term safe use of ceramic materials under high temperature conditions.

[0003] CN115673603A discloses a high temperature resistant and anti-oxidation composite brazing material and brazing method for alumina ceramics. The above scheme uses a special composite brazing material to complete brazing. During the heating process, the furnace temperature is raised to a brazing temperature of 1200-1600°C at a heating rate not exceeding 10°C / min, and the heat treatment is carried out for 5-60 minutes; then, the furnace temperature is lowered to 500°C at a cooling rate of 5°C / min; finally, the welded product is cooled to room temperature with the furnace. The heat treatment process of the above brazing method will cause thermal mismatch, and the residual stress will cause cracks in the joint. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a method for brazing alumina ceramics, which solves the problem of cracking of brazed joints and avoids oxidation corrosion of welds, and can prepare alumina ceramics with good performance.

[0005] The technical solution of this application is:

[0006] A brazing method for alumina ceramics, used for connecting an alumina ceramic substrate and a metal weldment, comprises the following steps:

[0007] Step 1: metallizing the surface of the alumina ceramic substrate;

[0008] Step 2: sequentially assembling a BNi-9 welding sheet and a metal weldment on an alumina ceramic substrate to obtain a semi-finished product;

[0009] Step 3: In a vacuum environment, heat the semi-finished product to 1060-1090°C and keep it warm for 30-80 minutes;

[0010] Step 4: Under vacuum environment, cool the semi-finished product to 1030-1045°C at a rate of 1-3°C / min, keep warm for 10-30min; then cool it to 830-870°C at a rate of 4-6°C / min, keep warm for 30-60min, then cool it to 540-600°C at a rate of 3-5°C / min, keep warm for 40-75min, and finally cool it naturally.

[0011] The cooling process of the present application adopts a step-by-step slow cooling process, thereby effectively releasing the residual stress generated during cooling and reducing the cracks caused by thermal mismatch between the alumina ceramic substrate and the metal weldment. At the same time, the BNi-9 welding sheet has the advantages of good flowability and stability at high temperatures, and is particularly suitable for preparing alumina ceramic materials used in high-temperature working environments.

[0012] In the above-mentioned brazing method of alumina ceramics, the step 1 comprises the following steps:

[0013] Step 11: depositing a metal layer on the alumina ceramic substrate;

[0014] Step 12: Nickel is plated on the metal layer.

[0015] In the above-mentioned alumina ceramic brazing method, the step 3 is to heat up to 800-900°C at a rate of 5-10°C / min, keep warm for 10-60min, then heat up to 1000-1050°C at a rate of 2-5°C / min, keep warm for 30-80min, and finally heat up to 1060-1090°C at a rate of 1-3°C / min for 5-30min.

[0016] In the above-mentioned alumina ceramic brazing method, the step 11 is to evenly apply the molybdenum-manganese slurry on the surface of the alumina ceramic substrate by screen printing, and then sinter at high temperature to obtain a molybdenum-manganese metal layer; the thickness of the molybdenum-manganese metal layer is 10 to 50 μm.

[0017] In the above-mentioned brazing method of alumina ceramics, before step 1, the alumina ceramic substrate, the BNi-9 welding sheet and the metal weldment are ultrasonically cleaned with acetone and ethanol solution and then dried.

[0018] In the above-mentioned brazing method of alumina ceramics, the metal weldment is inconel625 alloy with a thickness of 0.1 to 1 mm.

[0019] In the above-mentioned brazing method of alumina ceramics, the thickness of the BNi-9 welding sheet is 0.1 to 0.2 mm.

[0020] In the above-mentioned brazing method of alumina ceramics, the vacuum degree in step 3 and step 4 is less than 5*10-3 Pa.

[0021] In the above-mentioned alumina ceramic brazing method, the purity of the alumina ceramic substrate is ≥95%.

[0022] In addition, the present application also provides an alumina ceramic, which is produced by the above-mentioned brazing method of alumina ceramic.

[0023] The alumina ceramics prepared in the present application can repeatedly withstand thermal shocks and maintain a high level of tensile strength and air tightness in a high temperature environment.

[0024] One of the above technical solutions of the present application has at least one of the following advantages or beneficial effects:

[0025] The present application uses BNi-9 welding sheet as brazing solder to prepare alumina ceramics with good thermal stability at high temperatures and excellent anti-oxidation properties; at the same time, the preparation process of the present application adopts a step-by-step slow cooling method to prevent cracks from occurring between the alumina ceramic substrate and the metal weldment due to thermal mismatch. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of the structure of the alumina ceramic of the present application.

[0027] Description of reference numerals:

[0028] 1. Alumina ceramic substrate; 2. Metal layer; 3. Nickel layer; 4. BNi-9 welding sheet; 5. Metal weldment. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0030] In the following tests, a universal testing machine was used to test the tensile strength, and a helium mass spectrometer leak detector was used to test the air tightness.

[0031] Example 1

[0032] A brazing method for alumina ceramics is used to connect an alumina ceramic substrate and a metal weldment. In an embodiment, the purity of the alumina ceramic substrate is ≥95%; the metal weldment is an inconel625 alloy and is processed into a pipe with a thickness of 0.2 mm; the thickness of a BNi-9 welding sheet (whose main component is nickel, and the content of other elements accounts for: chromium 13.5% to 16.5%, boron 3.25% to 4%, iron 1.5%) is 0.1 mm; comprising the following steps:

[0033] Cleaning: The alumina ceramic substrate, BNi-9 welding sheet and metal weldment are ultrasonically cleaned in an acetone and ethanol solution for 30 minutes and dried for later use.

[0034] Metallization: The molybdenum-manganese slurry is evenly coated on the surface of the alumina ceramic substrate by screen printing. After high-temperature sintering, a molybdenum-manganese metal layer is obtained. The thickness of the molybdenum-manganese metal layer is 25um, and then nickel plating is performed to complete the metallization treatment.

[0035] Assemble, assemble BNi-9 welding sheet and metal welding parts on alumina ceramic substrate in sequence to obtain semi-finished products, such as Figure 1 As shown, in actual application, this embodiment also requires placing a 2kg graphite block on the semi-finished product to press the semi-finished product;

[0036] After heating and assembly, the semi-finished product is placed in a vacuum brazing furnace and the vacuum degree of the vacuum brazing furnace is reduced to less than 5*10 -3 After pa, the temperature is raised to 850℃ at a rate of 5℃ / min and kept for 30min to maintain the vacuum degree in the vacuum brazing furnace stable and ensure uniform preheating of the material; then the temperature is raised to 1035℃ at a rate of 4℃ / min and kept for 40min to ensure the temperature is consistent everywhere; finally, the temperature is raised to 1075℃ at a rate of 2℃ / min and kept for 15min to ensure that the BNi-9 pad is fully melted and dispersed;

[0037] Cool down, after the heating and insulation is completed, cool down to 1035℃ at a rate of 2℃ / min, and keep it warm for 10min; then cool down to 850℃ at a rate of 4℃ / min, and keep it warm for 30min; then cool down to 560℃ at a rate of 4℃ / min, and keep it warm for 60min. Finally, cool to room temperature with the furnace and take out to obtain alumina ceramics.

[0038] The tensile strength of alumina ceramics is 76 MPa and the air tightness is 4.5*10 -11 Pa.m 3 / s.

[0039] Example 2

[0040] It is basically the same as Example 1, except that, during the cooling process, the temperature is cooled to 1035°C at a rate of 3°C / min and kept at this temperature for 10 minutes; then the temperature is cooled to 830°C at a rate of 6°C / min and kept at this temperature for 30 minutes; then the temperature is cooled to 540°C at a rate of 5°C / min and kept at this temperature for 60 minutes. Finally, after cooling to room temperature with the furnace, the alumina ceramic is taken out and obtained.

[0041] Alumina ceramics were tested, with a tensile strength of 63 MPa and air tightness of 8.9*10 -10 Pa.m 3 / s.

[0042] Example 3

[0043] It is basically the same as Example 1, except that, during the cooling process, the temperature is cooled to 1035°C at a rate of 1°C / min and kept at this temperature for 10 minutes; then the temperature is cooled to 870°C at a rate of 4°C / min and kept at this temperature for 30 minutes; then the temperature is cooled to 600°C at a rate of 3°C / min and kept at this temperature for 60 minutes. Finally, after cooling to room temperature with the furnace, the alumina ceramic is taken out and obtained.

[0044] Alumina ceramics were tested, with a tensile strength of 71 MPa and air tightness of 1.1*10 -10 Pa.m 3 / s.

[0045] Comparative Example 1

[0046] It is basically the same as Example 1, except that, during the cooling process, the alumina ceramic is taken out after being directly cooled to room temperature in the furnace.

[0047] Testing alumina ceramics, its tensile strength is 45mpa, air tightness is 2.0*10 -9 Pa.m 3 / s.

[0048] Comparative Example 2

[0049] The method is basically the same as Example 1, except that, during the cooling process, the temperature is cooled to 540-600° C. at a rate of 3° C. / min, kept at that temperature for 60 minutes, and finally cooled naturally.

[0050] Alumina ceramics were tested, with a tensile strength of 62 MPa and air tightness of 8.2*10 -10 Pa.m 3 / s.

[0051] Comparative Example 3

[0052] The method is basically the same as Example 1, except that, during the cooling process, the temperature is cooled to 540-600° C. at a rate of 5° C. / min, kept at that temperature for 60 minutes, and finally cooled naturally.

[0053] Alumina ceramics were tested, with a tensile strength of 58 MPa and air tightness of 7.6*10 -10 Pa.m3 / s.

[0054] Comparative Example 4

[0055] It is basically the same as Example 1, except that, during the cooling process, the temperature is cooled to 1035°C at a rate of 5°C / min and kept at this temperature for 10 minutes; then the temperature is cooled to 850°C at a rate of 8°C / min and kept at this temperature for 30 minutes; then the temperature is cooled to 560°C at a rate of 6°C / min and kept at this temperature for 60 minutes. Finally, after cooling to room temperature with the furnace, the alumina ceramic is taken out and obtained.

[0056] Alumina ceramics were tested, with a tensile strength of 55 MPa and air tightness of 7.3*10 -10 Pa.m3 / s.

[0057] Comparative Example 5

[0058] It is basically the same as Example 1, except that an oxygen-free copper welding sheet with a thickness of 0.1 mm is used.

[0059] Alumina ceramics were tested, with a tensile strength of 94 MPa and air tightness of 1.8*10 -11 Pa.m 3 / s.

[0060] Simulated thermal cycle test: The alumina ceramics obtained in the above examples were subjected to repeated thermal shock at a heating rate and a cooling rate of 5°C / min in the temperature range of 25 to 1000°C for 20 cycles. The results are as follows:

[0061] Table 1: Status of weld after thermal shock and change of air tightness of alumina ceramics

[0062]

[0063] Result analysis:

[0064] Comparative Examples 1 to 4:

[0065] Example 1: The cooling rate determines the rate at which material stress is generated. When cooling down, a step-by-step slow cooling method is used to effectively reduce the residual stress of the joint. No cracks are found in the weld after the thermal shock, indicating that the stress of the joint has been effectively eliminated.

[0066] Example 2 cools at the fastest speed: Compared with Example 1, the air tightness of the sample obtained by adopting a faster cooling rate during cooling is also reduced more, and the residual stress elimination effect is poor. In subsequent tests, microcracks generated during repeated heating and cooling will affect the air tightness.

[0067] The cooling rate of Example 3 is the slowest: Compared with Example 1, the cooling rate of Example 3 is slower, but its air tightness is slightly lower. The reason is that the cooling rate of brazing is reduced, and the residence time of the solder in the high temperature stage is extended in disguise. The solder is prone to dissolving the metallization layer at the position where the metallization layer is thinner, thereby reducing the air tightness of the joint.

[0068] Comparative Example 1: After brazing, the furnace was naturally cooled. During the test, the ceramic at the weld cracked and the joint fell off when the thermal shock was carried out for the 7th time. This is because the thermal expansion coefficient of alumina ceramic and inconel625 metal is quite different. During the cooling stage, the rapid cooling speed will produce large residual stress at the joint.

[0069] Comparative Example 2 (no gradient cooling but controlled cooling speed): During cooling, the sample was cooled directly at a speed of 3°C / min without staying in the high temperature section. The air tightness of the obtained sample decreased more after the thermal shock, indicating that step-by-step cooling is beneficial to eliminating sealing stress.

[0070] Comparative Example 3 (faster cooling speed than Comparative Example 2): Compared with Comparative Example 2, the temperature is directly cooled at a rate of 5°C / min without staying in the high temperature section during cooling. The air tightness after thermal shock is lower than that of Comparative Example 2. The reason is that the cooling speed is faster and the residual stress is greater.

[0071] Comparative Example 4 (cooling rate beyond the protection range): a step-by-step cooling was set during cooling, but the cooling was accelerated. After the thermal shock, tiny cracks were found in the ceramic at the joints, and the air tightness decreased significantly. It can be seen that the cooling rate is a more important factor in eliminating sealing stress.

[0072] Comparative Example 5 (other types of high temperature resistant solder sheets): Compared with BNi-9 solder, the sample brazed with oxygen-free copper solder sheets has higher tensile strength, but the air tightness is greatly reduced after thermal shock. The reason is that the copper in the weld is oxidized at high temperature, the oxide layer is not dense, and the weld is gradually oxidized and corroded, resulting in reduced air tightness. Compared with oxygen-free copper or other nickel-based solders, BNi-9 solder contains more chromium. The increase in chromium content greatly improves the oxidation resistance and corrosion resistance of the joint at high temperature. The absence of silicon and the lower boron content can also avoid the large-scale generation of brittle phases in the joint. The joint brazed with it can be used for a long time under high temperature conditions.

[0073] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the claims and their equivalents.

Claims

1. A brazing method for alumina ceramics, used to connect an alumina ceramic substrate and a metal weldment, characterized in that: The steps include: Step 1: metallizing the surface of the alumina ceramic substrate; Step 2: sequentially assembling a BNi-9 welding sheet and a metal weldment on an alumina ceramic substrate to obtain a semi-finished product; Step 3: In a vacuum environment, heat the semi-finished product to 1060-1090°C and keep it warm for 5-30 minutes; Step 4: Under vacuum environment, cool the semi-finished product to 1030-1045°C at a rate of 1-3°C / min, keep warm for 10-30min; then cool it to 830-870°C at a rate of 4-6°C / min, keep warm for 30-60min, then cool it to 540-600°C at a rate of 3-5°C / min, keep warm for 40-75min, and finally cool it naturally.

2. The brazing method of alumina ceramics according to claim 1, characterized in that: The step 1 comprises the following steps: Step 11: depositing a metal layer on the alumina ceramic substrate; Step 12: Nickel is plated on the metal layer.

3. The brazing method of alumina ceramics according to claim 1, characterized in that: In step 3, the temperature is raised to 800-900°C at a rate of 5-10°C / min, kept at this temperature for 10-60min, then raised to 1000-1050°C at a rate of 2-5°C / min, kept at this temperature for 30-80min, and finally raised to 1060-1090°C at a rate of 1-3°C / min for 5-30min.

4. The brazing method of alumina ceramics according to claim 2, characterized in that: In step 11, the molybdenum-manganese slurry is evenly coated on the surface of the alumina ceramic substrate by screen printing, and then sintered at high temperature to obtain a molybdenum-manganese metal layer; the thickness of the molybdenum-manganese metal layer is 10 to 50 μm.

5. The brazing method of alumina ceramics according to claim 1, characterized in that: Before step 1, the alumina ceramic substrate, the BNi-9 welding sheet and the metal weldment are ultrasonically cleaned with acetone and ethanol solution, and then dried.

6. The brazing method of alumina ceramics according to claim 1, characterized in that: The metal weldment is made of inconel625 alloy and has a thickness of 0.1 to 1 mm.

7. The method for brazing alumina ceramics according to claim 1, characterized in that: The thickness of the BNi-9 welding sheet is 0.1-0.2 mm.

8. The brazing method of alumina ceramics according to claim 1, characterized in that: The vacuum degree in step 3 and step 4 is less than 5*10 -3 pa.

9. The method for brazing alumina ceramics according to claim 1, characterized in that: The purity of the alumina ceramic substrate is ≥95%.

10. An alumina ceramic, characterized in that: The alumina ceramic is prepared by the brazing method of any one of claims 1 to 9.